2020
DOI: 10.1016/j.brs.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

SICI during changing brain states: Differences in methodology can lead to different conclusions

Abstract: Background: Short-latency intracortical inhibition (SICI) is extensively used to probe GABAergic inhibitory mechanisms in M1. Task-related changes in SICI are presumed to reflect changes in the central excitability of GABAergic pathways. Usually, the level of SICI is evaluated using a single intensity of conditioning stimulus so that inhibition can be compared in different brain states. Objective: Here, we show that this approach may sometimes be inadequate since distinct conclusions can be drawn if a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The results showed that show that SICI changes that occurred during the task could be either larger or smaller than at rest depending on the intensity of the CS. Together, these findings also confirmed that testing SICI using a wide range of CS intensities provides a more nuanced interpretation of possible GABAergic changes in M1 than testing with a single CS intensity (Ibáñez et al, 2019). We believe that the adaptive threshold hunting paradigm could be useful in further studies to assess SICI during various cognitive and motor states.…”
Section: Perspectivesupporting
confidence: 71%
See 1 more Smart Citation
“…The results showed that show that SICI changes that occurred during the task could be either larger or smaller than at rest depending on the intensity of the CS. Together, these findings also confirmed that testing SICI using a wide range of CS intensities provides a more nuanced interpretation of possible GABAergic changes in M1 than testing with a single CS intensity (Ibáñez et al, 2019). We believe that the adaptive threshold hunting paradigm could be useful in further studies to assess SICI during various cognitive and motor states.…”
Section: Perspectivesupporting
confidence: 71%
“…Importantly, other cognitive conditions that share analogous control mechanisms and neural circuits with overt movements, such as motor preparation or action observation, are known to selectively modulate corticospinal excitability and to affect SICI (Naish et al, 2014;Duque et al, 2017). Supporting this view, a recent study measured SICI using a range of CS intensities at rest and during a warned simple reaction time task (Ibáñez et al, 2019). The results showed that show that SICI changes that occurred during the task could be either larger or smaller than at rest depending on the intensity of the CS.…”
Section: Perspectivementioning
confidence: 99%
“…This choice was made to avoid any fatigue effect that might have potentially confounded the results obtained. Moreover, both SICI MEPTEST and SICI Mmax modulations also depend on CS intensity and interstimulus interval (ISI) duration [ 6 , 12 , 51 , 52 , 53 ], two fixed parameters whose effects were not assessed in the current study. The CS intensity was fixed at 70% of MT calculated according to each levels of contraction.…”
Section: Discussionmentioning
confidence: 99%
“…A warned signal reaction-time task (wSRTT) was used for the intervention [6]. Each trial in the wSRTT consisted of five phases: 1) resting phase (500 ms); 2) warning stimulus (WS, 500 ms); 3) delay period (1000 ms); 4) reaction phase triggered by a "Go" cue; and 5) feedback phase showing participants their reaction time ( Fig.…”
Section: Dear Editormentioning
confidence: 99%